Niger : Second Review Under the Extended Credit Facility Arrangement, and Request for Modification of a Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report ;, 2018)
With one of the lowest scores in the Human Development Index, Niger is facing daunting development challenges, exacerbated by security concerns from terrorist incursions, low prices for key uranium exports, climate change, and excessive population growth. Nonetheless, GDP grew by a respectable 5 percent in the past two years and should gradually rise to 5 3/4 percent as reforms and substantial donor support bear fruit. The government is reform oriented and enjoys a comfortable parliamentary majority, but ongoing demonstrations signal a degree of social discontent.